Advanced Control Engineering Methods in Electrical Engineering Systems - Chadli, Mohammed; Bououden, Sofiane; Ziani, Salim; Zelinka, Ivan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the Third International Conference on Electrical Engineering and Control (ICEECA2017). It covers new control system models and troubleshooting tips, and also addresses complex system requirements, such as increased speed, precision and remote capabilities, bridging the gap between the complex, math-heavy controls theory taught in formal courses, and the efficient implementation required in real-world industry settings. Further, it considers both the engineering aspects of signal processing and the practical issues in the broad field of information transmission and novel technologies for communication networks and modern antenna design. This book is intended for researchers, engineers, and advanced postgraduate students in control and electrical engineering, computer science, signal processing, as well as mechanical and chemical engineering.
Backstepping Control of Abnormal Behaviours in DC-DC Boost Converter -- Phase-plane methods to analyse power system transient stability -- H∞ fuzzy control for Electrical Power Steering subject to actuator saturation -- Power Quality Enhancement with UPQC Systems based on Multi-level (NPC) Inverters -- Hinfiny Based State Feedback Control of LPV Time-Delay Systems Via Parameter-Dependent Lyapunov Krasovskii Functionals.
Keywords: Control engineering; Signal processing; Computational intelligence; Telecommunication; Control and Systems Theory; Signal, Speech and Image Processing; Computational Intelligence; Communications Engineering, Networks